2016
DOI: 10.2147/ndt.s121779
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise promotes neuroprotection against cerebral ischemia–reperfusion injury via downregulation of pro-inflammatory mediators

Abstract: BackgroundStroke is one of the major causes of morbidity and mortality worldwide, which is associated with serious physical deficits that affect daily living and quality of life and produces immense public health and economic burdens. Both clinical and experimental data suggest that early physical training after ischemic brain injury may reduce the extent of motor dysfunction. However, the exact mechanisms have not been fully elucidated. The aim of this study was to investigate the effects of aerobic exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…2 . GFAP, a marker of reactive astrocytes, was revealed to be significantly increased following cerebral ischemia ( 26 ); however, this effect was significantly attenuated following treadmill exercise (P<0.001; Fig. 2A ).…”
Section: Resultsmentioning
confidence: 96%
“…2 . GFAP, a marker of reactive astrocytes, was revealed to be significantly increased following cerebral ischemia ( 26 ); however, this effect was significantly attenuated following treadmill exercise (P<0.001; Fig. 2A ).…”
Section: Resultsmentioning
confidence: 96%
“…Studies have shown that exercise reduces gene expression Cytokine IL-1β. Hence, it is possible that exercise decreases the inflammatory response through HMGB1 and exerts its protective effect [16,34].Pan et al reported that aerobic exercise reduces cardiac tissue HMGB1 protein in diabetic patients [15], and Gialoria et al reported a decrease in this gene in patients with myocardial infarction [35]. Heat shock proteins (HSPs) increase after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Treadmill exercise was initiated 24 h after ischemia for 30 min and continued daily for 6 consecutive days (Zhang et al, 2016). Mild exercise included running at 3 m/min for 5 min, 5 m/min for 5 min, and then 8 m/min for 20 min at 0° slope (18).…”
Section: Methodsmentioning
confidence: 99%